THE EFFECT OF MSME FINANCIAL CONDITIONS DURING THE COVID-19 PANDEMIC ON MSME PERFORMANCE IN PALEMBANG - Setiawan , Alfredo Valentino; Panjaitan, Delfi (Jurnal Informasi Akuntansi (JIA), 2023)
This study aims to determine the effect of the financial condition of MSMEs during the Covid-19 pandemic on MSME performance by focusing on MSMEs in Palembang for the research period in 2021. The data used are primary data. The population in this study is MSMEs engaged in culinary, fashion, basic necessities, and mobile phone accessories. The sampling technique used was purposive sampling and 100 SMEs were obtained after determining the number of samples using the Slovin method . Hypothesis testing is done by analyzing the coefficient of determination and T test. The results of this study indicate that the financial condition of MSMEs affects the performance of MSMEs.